Cortisol, Depression, and Anxiety Levels Before and After Short-Term Intensive Nutritional Stabilization in Patients With Severe Anorexia Nervosa - Hemmingsen, Simone Daugaard; Jensen, Nikolai Arndal; Larsen, Pia Veldt; Sjögren, Jan Magnus; Lichtenstein, Mia Beck; Støving, René Klinkby (Frontiers in Psychiatry, 2022)
Introduction: Depression and anxiety are well known comorbid conditions in patients with anorexia nervosa (AN). Hypercortisolemia in patients with AN may be pathogenic and contribute to depression and anxiety symptomatology. Objective: The aim of this study was to investigate short-term changes in cortisol levels and depression and anxiety symptomatology following intensive re-nutrition in patients with severe AN and hospitalized in a specialized unit. Furthermore, we investigated the potential association between cortisol levels and psychometric parameters. Methods: A total of 36 patients with AN were enrolled in the study. Nine dropped out before follow-up. Patients underwent paraclinical and psychometric examinations at admission and discharge. Measurements included plasma cortisol, cortisol binding globulin (CBG), 24-hour urine cortisol, and self-report questionnaires regarding eating disorder, depression, anxiety, and stress symptoms. Patients were hospitalized in the unit for somatic stabilization and intensive re-nutrition. Mean admission length was 41 days. The study was registered at ClinicalTrials.gov (NCT02502617). Results: Cortisol levels in blood and urine did not change from admission to discharge in patients with severe AN. Symptoms of depression, anxiety, stress, and eating disorder remained elevated at discharge. There were no associations between changes in cortisol levels and changes in psychometrics. Discussion: Our results suggest that short-term intensive re-nutrition did not alter hypothalamic-pituitary-adrenal axis activity or mental health in patients with severe AN. Long-term stabilization and longer follow-up after hospital discharge may be needed to detect changes in cortisol levels and whether these changes are associated with depression and anxiety symptomatology. Greater knowledge about cortisol levels and mental health in patients with severe AN may help in the development of new treatment choices for the chronically ill patients. Future studies could investigate whether cortisol-lowering drugs have a therapeutic effect on mental health in AN.